Programações de ensino para refinamento das habilidades de leitura e escrita de um aluno com Transtorno de Asperger - Carvalho, Brunna Stella da Silva (2013)
The Asperger nuisance is considered a global development nuisance with loss in many areas: social interaction, communication and interests and restrict activities. People with the nuisance, in general, do not present problems of cognitive and verbal fluency is evident. The searches about the academics abilities of reading and writing to this population are scarce in the scientific literature. A student joined this research with a previous Asperger diagnostic, he was in his last year on high school, 9 years and 11 months old. The present search identified the positive points and the academic deficits in reading and writing of the student; present strategies, programs and teaching reviews of individualized teaching were made. It was implemented five programming of teaching to the specific difficulties of the student, with the progression criterion from the repertory development of the student. It was: 1) Module of Application 2 of the Reading Program and dictation managed by the software Aprendendo a ler e escrever em pequenos passos; 2)Complemented activity of auditory discrimination; 3) Program to exchange phonemic voiced and unvoiced; 4) Vocalic meeting program and 5) Read texts. The experimental designs used were a multiple base line to the programs 1 and 5 and the design of pre and post test to the programs 3 and 4. The general goals about reading were: 1) Read with precision complex words from the portuguese language and texts; 2) Read with fluency; 3) Read with understanding. About the writing: 1) Write with precision under control dictation. The specific goals were relacted to: discriminate accurately between words dictated and words printed that presented phonemes deaf and sound; read and write with precision with meeting vowel; write with a right sequence of words of configuration vowel-word-consonant-vowel. The results showed satisfactory and achieved the goal presented. The research showed still the importance of elaboration of teaching strategies based in the verification of needs and students potential, beyond teaching and consistent evaluations, systematic and consistent.